The Obligations of Armed Non-State Actors during Non- International Armed Conflict- A Critical Assessment - EBU, Alex Abang (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
This article critically assesses the obligations of armed non-state actors (ANSAs) during non-international armed conflicts (NIACs), exploring the legal frameworks that govern their conduct under International Humanitarian Law (IHL) and International Human Rights Law (IHRL). It examines key responsibilities imposed on ANSAs, including the protection of civilians, humane treatment of detainees, and adherence to limitations on warfare methods. Drawing on Common Article 3 of the Geneva Conventions and Additional Protocol II, the article delves into the specific obligations of ANSAs, highlighting their shared accountability with state actors in ensuring compliance with humanitarian principles. The discussion also addresses the challenges in enforcing these obligations and the legal implications of non-compliance by ANSAs. By linking the responsibilities of states and armed groups, the article provides a comprehensive analysis of how ANSAs are bound by international norms, particularly in the context of safeguarding civilians and adhering to lawful methods of warfare.